Non Infantile Desmoplastic Astrocytoma: a case Report (Indian Journal of Case Reports, 2015)
Desmoplastic infantile astrocytomas (DIA) are huge cerebral masses with cystic and solid components in infants with a benign course. Less than 50 cases of have been reported in the literature and most of the cases are children below 24 months. We are presenting a rare case of DIA which presented at the age of 4 years with vomiting and headache in neurosurgical OPD. He was diagnosed with a huge left temporal parietal tumor with midline shift which on histopathological examination was confirmed as DIA. Patient was operated and had good recovery and was followed up for two years.